2020
DOI: 10.1002/mp.14170
|View full text |Cite
|
Sign up to set email alerts
|

AirNet: Fused analytical and iterative reconstruction with deep neural network regularization for sparse‐data CT

Abstract: Purpose: Sparse-data computed tomography (CT) frequently occurs, such as breast tomosynthesis, Carm CT, on-board four-dimensional cone-beam CT (4D CBCT), and industrial CT. However, sparse-data image reconstruction remains challenging due to highly undersampled data. This work develops a datadriven image reconstruction method for sparse-data CT using deep neural networks (DNN). Methods: The new method so-called AirNet is designed to incorporate the benefits from analytical reconstruction method (AR), iterative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 45 publications
(106 reference statements)
1
33
0
Order By: Relevance
“…Second, the size of images reconstructed by an unrolled network is typically small. For example, the input image consists of small pixels for ADMM-net, 41 MetaInv-Net, 43 LEARN, 44 and AirNet, 46 limited by the memory size of the GPU. The reconstructed low-resolution results could not satisfy the requirement of many clinical applications, especially for CT imaging tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the size of images reconstructed by an unrolled network is typically small. For example, the input image consists of small pixels for ADMM-net, 41 MetaInv-Net, 43 LEARN, 44 and AirNet, 46 limited by the memory size of the GPU. The reconstructed low-resolution results could not satisfy the requirement of many clinical applications, especially for CT imaging tasks.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the applied CNN is modified by concatenating all previous estimates of the latent image as the input. We replace CNN(x k+ 1 2 , θ 2 k ) with a densely-connected [34], which was utilized in our previous work for sparse-data CT [35] and shown to outperform the standard CNN. The problem of vanishing gradient can be addressed by the modification.…”
Section: Dl-regularized Pfbsmentioning
confidence: 99%
“…Most OBL frameworks unroll IR, such as gradient descent, and learn the gradient of an image prior that is applied during each iteration. For SV-CT, Chen et al [4] demonstrated state-of-the-art performance with OBL. A more general approach to learning a data-driven inversion of linear inverse problems are Neumann networks introduced by Gilton et al [12].…”
Section: Related Workmentioning
confidence: 99%